2013
DOI: 10.1186/1471-2180-13-196
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi mitochondrial swelling and membrane potential collapse as primary evidence of the mode of action of naphthoquinone analogues

Abstract: BackgroundNaphthoquinones (NQs) are privileged structures in medicinal chemistry due to the biological effects associated with the induction of oxidative stress. The present study evaluated the activities of sixteen NQs derivatives on Trypanosoma cruzi.ResultsFourteen NQs displayed higher activity against bloodstream trypomastigotes of T. cruzi than benznidazole. Further assays with NQ1, NQ8, NQ9 and NQ12 showed inhibition of the proliferation of axenic epimastigotes and intracelulluar amastigotes interiorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…However, there is only limited evidence about changes in the structure of endoplasmic reticulum under treatment with juglone. Salomao et al, who investigated effect of naphthoquinone analogues on Trypanosoma cruzii, observed mitochondrial swelling and membrane potential collapse as well as large endoplasmic reticulum profiles surrounding different cellular structures (Salomao et al, 2013). Finally, we observed DNA fragmentation, which was revealed using two methods, the TUNEL test and DNA electrophoresis.…”
Section: Discussionmentioning
confidence: 78%
“…However, there is only limited evidence about changes in the structure of endoplasmic reticulum under treatment with juglone. Salomao et al, who investigated effect of naphthoquinone analogues on Trypanosoma cruzii, observed mitochondrial swelling and membrane potential collapse as well as large endoplasmic reticulum profiles surrounding different cellular structures (Salomao et al, 2013). Finally, we observed DNA fragmentation, which was revealed using two methods, the TUNEL test and DNA electrophoresis.…”
Section: Discussionmentioning
confidence: 78%
“…The lapachone-induced mitochondrial dilation and autophagy (mitophagy) mechanisms depend on the production of ROS (Salomão et al., 2013). The R72-treated parasites not only removed mitochondrial portions by mitophagy, but also showed mitochondria in the condensed configuration with distended cristae, long known to be metabolically inactive (Hackenbrock et al., 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, mitophagy and mitochondrial loss of function may lead to metabolic deficit, possibly promoting parasite necrosis. β-lapachone and its derivatives were shown to trigger apoptosis and autophagy in both parasites (Docampo et al., 1978, Menna-Barreto et al., 2009a, Salomão et al., 2013) and tumor cells (Li et al., 1999, Li et al, 2003; Park et al., 2011, Di Rosso et al., 2013), involving the formation of ROS (Araújo et al., 2012, Salomão et al., 2013). …”
Section: Discussionmentioning
confidence: 99%
“…For transmission electron microscopy observation, cells over coverslips were fixed and post-fixed after 48 h of drug treatment as described above, dehydrated in an ascending acetone series and embedded in PolyBed 812 resin. Ultrathin sections were stained with uranyl acetate and lead citrate and examined in Jeol JEM1011 transmission electron microscope (Tokyo, Japan) at Plataforma de Microscopia Eletrônica, IOC, FIOCRUZ (Salomão et al 2013). …”
Section: Methodsmentioning
confidence: 99%